2003
DOI: 10.1074/jbc.m302599200
|View full text |Cite
|
Sign up to set email alerts
|

Long Distance Communication between Muscarinic Receptors and Ca2+ Release Channels Revealed by Carbachol Uncaging in Cell-attached Patch Pipette

Abstract: We have investigated the characteristics of cytosolic Ca 2؉ signals induced by muscarinic receptor activation of pancreatic acinar cells that reside within intact pancreatic tissue. We show that these cells exhibit global Ca 2؉ waves and local apical Ca 2؉ spikes. This is the first evidence for local Ca 2؉ signaling in undissociated pancreatic tissue. The mechanism of formation of localized Ca 2؉ signals was examined using a novel approach involving photolysis of caged carbachol inside a patch pipette attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 33 publications
(33 reference statements)
2
51
0
1
Order By: Relevance
“…Two NAADP-sensitive Ca 2+ stores in pancreatic acinar cells receptors, specifically and exclusively located in a small region at the base, induces initiation of cytosolic Ca 2+ signals in the apical part of the cell (Ashby et al, 2003a). Ca 2+ -induced Ca 2+ release can only be initiated in the secretory granule area .…”
mentioning
confidence: 99%
“…Two NAADP-sensitive Ca 2+ stores in pancreatic acinar cells receptors, specifically and exclusively located in a small region at the base, induces initiation of cytosolic Ca 2+ signals in the apical part of the cell (Ashby et al, 2003a). Ca 2+ -induced Ca 2+ release can only be initiated in the secretory granule area .…”
mentioning
confidence: 99%
“…For example, in polarized epithelial cells (such as parotid and pancreatic acinar cells), oscillatory [Ca 2+ ] i signals are initiated at specific "trigger zones" located in the apical region of the cell. Significantly, this phenomenon can be readily activated by local stimulation of appropriate receptors at the basal end of the cell (1). For these signals to be influenced by Ca 2+ entry via the ARC channels, either Ca 2+ would have to diffuse from basally activated ARC channels to the apical trigger zone or arachidonic acid would have to diffuse from its site of generation, presumably close to the basal receptors, to activate apically localized ARC channels.…”
Section: What Do Arc Channels Do?mentioning
confidence: 99%
“…The classical pathway linking stimulation by neurotransmitters and hormones to changes in phosphoinositide metabolism and the subsequent InsP 3 induced Ca 2+ release was in large part documented by work carried out in exocrine cells, in particular, acinar cells isolated from the exocrine pancreas (49). In seminal work using permeabilized rat pancreatic acini, Streb and colleagues demonstrated that the addition of InsP 3 resulted in Ca 2+ release from a nonmitochondrial Ca 2+ store (43).…”
Section: General: the Role Of Insp3r In Pancreatic Acinar And Other Cmentioning
confidence: 99%
“…The fidelity and specificity of the Ca 2+ signal required for exocytosis is thought to be largely determined by the differential expression, localization and modulation exhibited by the 3 InsP 3 R isoforms (14). For the most part, InsP 3 Rs are predominantly localized to the ER, although the golgi, nucleus, plasma membrane, peroxisomes and endolysosomal vesicles have also been reported to express small levels of InsP 3 Rs. Pancreatic acinar cells are highly polarized, both functionally and morphologically and InsP 3 Rs are predominantly expressed in ER extensions in the apical regions juxtaposed to the acinar lumen (22,24,32,57 …”
Section: General: the Role Of Insp3r In Pancreatic Acinar And Other Cmentioning
confidence: 99%
See 1 more Smart Citation